Force plate analyses before and after surgical treatment of unilateral fragmented coronoid process - Theyse, L. F. H.; Hazewinkel, H. A. W.; van den Brom, W. E. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
In this prospective study force plate analysis was used to investigate the locomotor aspects of unilateral fragmented medial coronoid process (FCP) and the effects of surgical treatment in seven dogs. The diagnosis unilateral FCP. was based on clinical and radiological examination of both elbow joints and confirmed during surgery. Radiological screening of the elbow joints was repeated at six months after surgery to determine the osteoarthritis (OA) score and to exclude any bilateral involvement. Force plate analyses were performed at three consecutive intervals: prior to surgery, at six weeks and at six months after surgery. The peak braking force Fymax, peak propulsive force-Fymin, peak vertical force-Fzmax and the corresponding impulses Iymax, Iymin and Iz were determined. The symmetry index SI of these forces and impulses (ratio affected side : contralateral side) in the front limbs was assessed to evaluate the locomotion. The combination of the Sis of Fymin, Fymax, Iymin, Iymax and Iz proved to be more sensitive in determining front limb lameness due to unilateral FCP than the SI of the peak vertical force Fzmax. The SI of Fzmax had returned to within the normal range at six months after surgery for all seven dogs, whereas the other parameters showed persisting abnormalities in two dogs. In this study the improvement after surgical treatment of the SI of both Fymin and Iymin was significant at P<0.05. All of the joints showed progressive radiological signs of OA at six months after surgery.The effects of unilateral fragmented medial coronoid process on the ground reaction forces of the front limbs and the effects of surgical treatment were evaluated using force plate analysis. Surgical treatment seemed to have a favorable outcome, despite radiological progression of osteoarthritis.
Keywords: Fragmented medial coronoid process; force plate analysis; elbow dysplasia; dog